AN ANALYSIS OF THE EFFECTS OF THE APPLICATION OF MOBILE PHONES IN CHILDREN IN SIDOMULYO VILLAGE AND KERTOSARI ESTATE HOUSING PONOROGO - Desriyanti .; Novita Popi Wulandari; Septian Hadi Wirdyanto (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2019)
Mobile Phone is a communication tool that is currently developing rapidly, both among parents, adolescents, and children. This study aimed to determine the effects of handphones on children in Sidomulyo village and Kertosari housing Ponorogo. This study used a moderating variable that is the roles of parents. The study population were parents in the village of Sidomulyo and Kertosari Estate Housing Ponorogo. The samples selected were parents aged 3-12 years. The analytical method used descriptive statistical analysis, data quality test or data validity test, regression analysis and then proceeded with hypothesis testing with the application of SPSS (Statistical Product and Service Solution). The first hypothesis testing showed that the use of mobile phones affected the social and emotional level of children. The second hypothesis testing showed that the role of parents could control children in using mobile phones with the children's social and emotional levels.